2003
DOI: 10.1097/01.psy.0000074758.02451.76
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and Arterial Properties in Response to Mental Stress in Individuals with Mild Hypertension

Abstract: Hemodynamic and arterial responses to mental stress in individuals with normal BP and mild hypertension were similar. Several parameters, however, were different in basal state. These differences (ie, higher PP, lower compliance, and higher AI in the mild hypertensive group) could be due to the chronic effect of sympathetic stimulation on central arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 34 publications
2
22
0
1
Order By: Relevance
“…Overall, the laboratory task used in this investigation was associated with increased cardiovascular functioning (i.e., blood pressure, pulse rate, and vascular resistance) in both boys and girls. Consistent with Tsai et al [39], who examined hemodynamic and arterial properties associated with mental stress in normotensives and mild hypertensives, this task was also related to a statistically significant decrease in arterial elasticity among boys in the present study. Future studies should explore the possible mitigating effects of sex steroids on the association between gender and task-induced changes in LAE.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, the laboratory task used in this investigation was associated with increased cardiovascular functioning (i.e., blood pressure, pulse rate, and vascular resistance) in both boys and girls. Consistent with Tsai et al [39], who examined hemodynamic and arterial properties associated with mental stress in normotensives and mild hypertensives, this task was also related to a statistically significant decrease in arterial elasticity among boys in the present study. Future studies should explore the possible mitigating effects of sex steroids on the association between gender and task-induced changes in LAE.…”
Section: Discussionsupporting
confidence: 93%
“…Previous results have been equivocal, with reports of both similar (Tsai et al . ; Khan et al . ) and exaggerated (Kohler et al .…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that subjects with hypertension are highly susceptible to noise exposure perhaps due to instability of blood pressure when exposed to exogenous stimuli, including noise exposure. Various studies have suggested that subjects with hypertension have exaggerated blood pressure reactivity to stress compared with normotensives [25][26][27][28][29] . In addition, a study reported that the excess mortality from coronary heart disease and stroke associated with mental stress tended to be more evident among those with hypertension who may have more advanced atherosclerosis compared with those with normal blood pressure 12) .…”
Section: Discussionmentioning
confidence: 99%